2022
DOI: 10.1021/acsomega.2c06359
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Optimization, and Evaluation of Paclitaxel and Curcumin Coloaded PLGA Nanoparticles for Improved Antitumor Activity

Abstract: Codelivery of chemotherapeutic drugs in nanoparticles can enhance the therapeutic effects against tumors. However, their anticancer properties and physiochemical characteristics can be severely influenced by many formulation parameters during the preparation process. It is a complicated development phase to select the optimal parameters for preparation of nanoparticles based on the commonly used one single parameter method, which consumes a lot of money, time, and effort, and sometimes even fails. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…7 Thus, this effort adds to those aiming to overcome some limitations hitherto experienced by the single emulsion technique. 28,32,33 By gathering these findings, the results obtained via single emulsion may become more competitive and closer to those obtained using other encapsulation procedures.…”
Section: Performance Of Curcuminmentioning
confidence: 75%
See 3 more Smart Citations
“…7 Thus, this effort adds to those aiming to overcome some limitations hitherto experienced by the single emulsion technique. 28,32,33 By gathering these findings, the results obtained via single emulsion may become more competitive and closer to those obtained using other encapsulation procedures.…”
Section: Performance Of Curcuminmentioning
confidence: 75%
“…Still, the single emulsion remains advantageous as it achieves high concentrations of NPs as well as by enabling a more practical circularization of the process: since the organic solvent used is not required to be partially miscible in water, its reuse is easier . Thus, this effort adds to those aiming to overcome some limitations hitherto experienced by the single emulsion technique. ,, By gathering these findings, the results obtained via single emulsion may become more competitive and closer to those obtained using other encapsulation procedures.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It was found that PNPs of doxorubicin and betanin reduced the cell sustainability amount of MCF-7 cells in breast cancer more than doxorubicin and betanin alone [ 113 ]. Hu H. et al delivered paclitaxel and curcumin using PLGA nanoparticles and was found that optimized formulation provided improved cytotoxicity, having reduced IC 50 in MCF-7 cells of breast cancer compared to free drugs [ 114 ].…”
Section: Nanocarrier-based Codelivery Of Chemotherapeutic Agent With ...mentioning
confidence: 99%